Successful One-Lung Ventilation with Fogarty Balloon for Thoracotomy Lobectomy in A 5-Year-Old Girl - Kurniyanta, I Putu; Putra, Kadek Agus Heryana; Burhan; Sidemen, I Gusti Putu Sukrama (Indonesian Journal of Anesthesiology and Reanimation, 2025)
Introduction: Pediatric thoracic surgery, particularly lung resection, has special difficulties due to anatomical and physiological differences compared to adults. One-lung ventilation (OLV) is often necessary to optimize surgical exposure while minimizing lung injury. Traditional methods, like double-lumen endotracheal tubes, can be difficult to use in children due to their smaller airways and the risk of trauma. Thus, alternative approaches, such as bronchial blockers like Fogarty occlusion catheters, have gained prominence. Objective: This case report aims to highlight the use of the Fogarty balloon in a pediatric patient undergoing lobectomy for organized pleural effusion linked to pneumonia. Case Report: A 5-year-old girl with recurrent pneumonia presented with persistent cough, intermittent fever, and respiratory distress. Physical examination revealed decreased breath sounds and mild cyanosis. Imaging confirmed a large organized pleural effusion, suspected to be empyema. The surgical team chose a right thoracotomy lobectomy to remove the affected lung tissue. Preoperative consultations included pediatric surgery, anesthesiology, and respiratory therapy to ensure comprehensive care. A multi-modal pain management strategy, emphasizing regional anesthesia through epidural blocks, was implemented. For OLV, the anesthetic team selected a Fogarty balloon catheter to minimize airway trauma. After intubating with a single-lumen endotracheal tube, the balloon was inserted into the right main bronchus and inflated to occlude it, allowing ventilation of the left lung. Discussion: The Fogarty balloon effectively provided lung isolation while preserving airway integrity, facilitating optimal surgical exposure and stable oxygenation. Continuous monitoring of oxygenation during OLV was crucial for patient safety. Conclusion: The use of a Fogarty balloon for bronchial blockade and epidural anesthesia was successful in this pediatric lobectomy case. These techniques enhanced surgical safety, efficacy, and postoperative recovery, suggesting that there must be ongoing research to establish standardized protocols for pediatric thoracic procedures.